The relationship between interpersonal communication skills and positive conformity of junior high school students - Monica, Mega Aria; Maharani, Laila; Primanisa, Reiska; Yani, Nadia Putri (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
Interpersonal communication skills play a crucial role in helping students navigate social interactions effectively. This study aimed to analyze the relationship between interpersonal communication skills and positive conformity among 7th-grade students at MTS Negeri 1 Bandar Lampung. Using a quantitative method with a correlational design, the study involved a sample of 41 students selected through probability sampling. The instruments included a scale for interpersonal communication skills and a positive conformity scale. The findings revealed that the average level of interpersonal communication skills among students was high, while their positive conformity levels ranged from moderate to high. Data analysis showed a correlation coefficient of R = 0.574 with a significance level of p < 0.00, indicating a significant positive relationship between interpersonal communication skills and positive conformity. In conclusion, the better a student's interpersonal communication skills, the higher their level of positive conformity.